Botrytis hypersensitive response inducing protein 1 triggers noncanonical PTI to induce plant cell death - Jeblick, Tanja; Leisen, Thomas; Steidele, Christina E.; Albert, Isabell; Mueller, Jonas; Kaiser, Sabrina; Mahler, Florian; Sommer, Frederik; Keller, Sandro; Hueckelhoven, Ralph; Hahn, Matthias; Scheuring, David (Plant Physiology, 2022)
The secreted Botrytis protein hypersensitive response inducing protein 1 activates plant defense to kill plant cells.
CRIS-Team WoS Importer:2022-11-11